2013
DOI: 10.1111/jan.12176
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with physical restraints in residential aged care facilities: a community‐based epidemiological survey in Taiwan

Abstract: To reduce the incidence of physical restraint in residential aged care facilities in Taiwan, educational programmes should target primary caregivers and families in facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
66
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 40 publications
8
66
1
1
Order By: Relevance
“…The reasons for using physical restraint and the most frequent shift (night shift) in which physical restraint was used in China were consistent with those reported from other countries. 1,3,14,16,21 However, we observed a slight difference in nurses' perceptions and practice in China compared with other countries. 22,23 In the qualitative study, nurses' perception toward the use of physical restraint in clinical care was predominately characterized by their main concern of protecting patient's safety, and the use of restraints apparently provided a certain sense of security to the nurses.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…The reasons for using physical restraint and the most frequent shift (night shift) in which physical restraint was used in China were consistent with those reported from other countries. 1,3,14,16,21 However, we observed a slight difference in nurses' perceptions and practice in China compared with other countries. 22,23 In the qualitative study, nurses' perception toward the use of physical restraint in clinical care was predominately characterized by their main concern of protecting patient's safety, and the use of restraints apparently provided a certain sense of security to the nurses.…”
Section: Discussioncontrasting
confidence: 66%
“…15 The most common treatment instruments removed by patients are endotracheal and nasogastric tubes. 3,4 Studies have indicated that physical restraints are more likely to be used in patients who are 65 years or older, 16 in patients with poor mobility and impaired cognitive status, and in patients who require extensive and complicated therapy and have a history and risk of falls. 15 Men are more likely to be physically restrained than women.…”
Section: Introductionmentioning
confidence: 98%
“…The highest usages reported in the literature were in Northern Ireland, Canada and Taiwan, with values between 62 and 68% [1, 26, 32], and the lowest in Germany with 26.2% [12]. The Netherlands was situated between them, with a prevalence of around 50% [24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…Physical restraint is used frequently in long-term care, mainly to prevent falls and, to a lesser extent, to reduce behavioural disturbances or avoid interference with patient treatments [1, 2]. Physical restraint is a controversial practice throughout the world [3, 4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation